Pola Pertumbuhan Rumput Signal (Brachiaria humidicola (Rendle) Schweick) pada Padang Penggembalaan dengan Aplikasi Sumber Nutrien Berbeda - L Abdullah (Media Peternakan, 2009)
An investigation on growth behavior parameters and its dynamic pattern of signal grass (Brachiaria humidicola) grown under influence of inorganic and organic nutrient supply was conducted during period of wet and early dry seasons in 2004. Five sets of treatments consisted of control (P0), mulch originated from pasture weed biomass (Chromolaena odorata) (PC), animal dung (PF), combination of mulch and dung (PC+F) and inorganic fertilizer (PA) were applied to one year existing signalgrass plots. Block randomized design with 4 replications was used in this experiment. The results showed that application of PA produced the highest length of stolons, node and tiller numbers. There was an improvement of growth by application of PC, PF and PC+F, but at lower level than those of PA. Application of PA caused short growth period (6-8 weeks) to reach maximum length of stolon, node and tiller numbers, but less persistent (10-12 weeks) if the grass had not been defoliated. On the other hand, application of organic nutrient led to slow growing grass, but it showed more persistent. The application of organic nutrient supply (PC, PF and PC+F) resulted the best growth of signal grass in comparison with control and more persistent than that of inorganic fertilizer (PA). Key words: Brachiaria humidicola, stolon, tiller, node, mulch